2022
DOI: 10.1371/journal.pone.0263621
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic landscapes of 51 pharmacogenes derived from whole-genome sequencing in a Thai population

Abstract: Differences in drug responses in individuals are partly due to genetic variations in pharmacogenes, which differ among populations. Here, genome sequencing of 171 unrelated Thai individuals from all regions of Thailand was used to call star alleles of 51 pharmacogenes by Stargazer, determine allele and genotype frequencies, predict phenotype and compare high-impact variant frequencies between Thai and other populations. Three control genes, EGFR, VDR, and RYR1, were used, giving consistent results. Every indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…The frequency of CYP2D6 alleles in our study was similar to previous reports in the Thai population [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. Furthermore, the proportions of CYP2D6 IM and CYP2D6 NM were consistent with those reported in Asians [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The frequency of CYP2D6 alleles in our study was similar to previous reports in the Thai population [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. Furthermore, the proportions of CYP2D6 IM and CYP2D6 NM were consistent with those reported in Asians [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…CYP2D6*2, CYP2D6*4, CYP2D6*5, and CYP2D6*10 were genotyped according to previous reports in Thai populations [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. The SNPs included 2850C > T (rs16947), 4180G > C (rs1135840), 100C > T (rs1065852), and 1846G > A (rs3892097).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…*36+*10 , *10 , and *36 were more prevalent in the Chinese and Malay populations, with the Chinese and Malays exhibiting approximately six-fold higher allele frequencies of *10 compared to Indians. This trend aligns with well-documented findings, which consistently report a high prevalence of the *36+*10 tandem in East Asian populations, including Japanese, Korean, and Chinese 8,9,16 . Furthermore, it supports the common identification of the *10 allele as a reduced-function variant in Asian populations 8,9 .…”
Section: Discussionsupporting
confidence: 91%
“…Hence, applying multi-tools for including more genes and variants seems reasonable. So far, most studies reported the advantages of using PGx bioinformatics tools in clinical investigations but as a separate entity [ 31 , 32 ]. For those reported the multi-tool utilization, again not all of the genes in all samples were evaluated in that way [ 33 ].…”
Section: Discussionmentioning
confidence: 99%